Case Report: Two-patch technique with BioGlue salvages a patient with acute inferior wall myocardial infarction complicated by ventricular septal rupture and cardiogenic shock - Chang, Rei-Yeuh; Chen, Tsung-Hsien; Tsai, Han-Lin; Chen, Yin-Chia (Frontiers in Cardiovascular Medicine, 2025)
Post-myocardial infarction ventricular septal rupture (VSR) is a rare but often fatal complication of acute myocardial infarction (AMI). Without surgical or percutaneous intervention, mortality is exceedingly high. Even with corrective procedures such as surgical repair or transcatheter septal closure, in-hospital mortality remains substantial, particularly in hemodynamically unstable patients. We report a case of acute inferior–posterior wall ST-segment elevation myocardial infarction complicated by a large VSR and cardiogenic shock. Immediate venoarterial extracorporeal membrane oxygenation support was initiated. The patient subsequently underwent surgical repair using a modified infarct exclusion technique, in which BioGlue was applied between two patches to reinforce closure, and the second patch was extended into the ventriculotomy to simplify the procedure. The patient survived and remained free of recurrent VSR at the 5-month follow-up. This modified approach offers a feasible and effective strategy for managing acute inferior–posterior VSR following AMI, particularly in critically ill patients.